With regard to maternal mortality - Ludmir, Abraham (2015)
In the last 30 years, we have witnessed countless exception symposia, panels, roundtables, forums, etc. etc. held to discuss the how to reduce maternal and perinatal mortality in our country, not chords figures advancing medical knowledge. In parallel we have had the opportunity to enjoy a pleasant experience: that even with structural constraints, poor implementation and facing the same type of patients with low economic level, it is feasible, and would say that reducing mortality quite significantly.